Prosedur Pemeriksaan CT Scan Kepala Polos pada Kasus Microcephaly di Instalasi Radiologi RS Roemani Muhammadiyah Semarang : (Studi Kasus pada Pasien Pediatrik Usia 5 Bulan) - Shintanaya Anggraeni; Sofie Nornalita Dewi; Ike Ade Nur Liscyaningsih (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Microcephaly is a condition in which a child's head circumference is smaller than the average for age and gender. The diagnosis can be made using a CT Scan, which should be adjusted to the patient's age according to the IAEA protocol (2012), with an ideal effective dose of 1.8–3.8 mSv for a tube current of 200 mAs. However, at the Radiology Installation of Roemani Muhammadiyah Hospital Semarang, the examination was carried out without differentiating age, resulting in an excess dose of 9.317 mSv. This study aims to evaluate the procedures, diagnostic information, and radiation protection in plain head CT Scans of pediatric patients with microcephaly. This study used a qualitative approach through observation, interviews, and documentation of 3 radiographers, 1 PPR, and 1 radiologist. The results showed no protection for patients and only basic protection for companions. CT Scans showed decreased brain volume and ventriculomegaly. It is recommended that the CT Scan protocol be adjusted to the child's age to reduce the radiation dose, through the setting of exposure factors, slice thickness, and pitch.